Impact of mango peel pectin and Bacillus iranensis on growth, immunity, and gene expression in Nile tilapia (Oreochromis niloticus) - Anisa Rilla Lubis; Nguyen Vu Linh; Khambou Tayyamath; Supreya Wannavijit; Punika Ninyamasiri; Chanagun Chitmanat; Wanaporn Tapingkae; Einar Ringø; Hien Van Doan; Maria Ángeles Esteban (Aquaculture Reports)
This study evaluates the impact of mango peel-derived pectin and Bacillus iranensis on the growth performance, immune response, histology, gene expression, and ammonia resistance of Nile tilapia (Oreochromis niloticus). A total of 320 fingerlings (average weight 30.5 ± 0.014 g) were divided into four groups and fed different diets for eight weeks: a control diet, a diet with 10 g kg⁻¹ mango pectin, a diet with 1.6 × 10⁹ CFU mL⁻¹ of Bacillus iranensis, and a combined diet of both supplements (10 g kg⁻¹ mango pectin + 1.6 ×10⁹ CFU mL⁻¹ of Bacillus iranensis). The results indicated that the group receiving the combined diet (T4) showed the highest growth performance, with significantly greater final weight, weight gain, and specific growth rate compared to the control group (P < 0.05). Immune response, measured by lysozyme, peroxidase activities, and alternative complement pathway activity (ACH50) in both skin mucus and serum, was also highest in the T4 group. ACH50 values were notably higher in the T4 group, indicating enhanced immune function. Gene expression analysis revealed that T4 significantly upregulated GPX and GSR in the head kidney, while GST-α expression remained unchanged across all treatments. For immune-related genes, TLR7 was upregulated in the head kidney of T4 fish, but NF-κB showed no significant differences across treatments, and MHC-IIα was downregulated in both tissues of supplemented groups compared to the control. These findings suggest that the dietary inclusion of mango peel pectin and Bacillus iranensis as a synbiotic supplement can significantly enhance growth performance, immunity, and the expression of certain immune and antioxidant related genes in Nile tilapia. This highlights their potential as effective feed additives for improving fish health and supporting sustainable aquaculture practices.